KEABSAHAN PENGANGKATAN WÂLÎMUHAKKAM DI MADURA BERDASARKAN FIKIH SYÂFI’Î - Moh. Zahid (Karsa: Journal of Social and Islamic Culture)
Abstract There are several events of sirrî (secret) marriage that employ wâlî (best man) muhakkam in Madurese society. It relies on the basis of fiqh (law) clauses especially Syâfi’î school of law. This kind of marriage is considered lawful but the term of wâlî (male relative legally responsible for a bride) muhakkam is unknown in legal constitution of Indonesia. The common reason behind it is that wali does not allow marriage permission and/or wali has fulfilled a required distance 2 marhalah (masâfat al-qashr) with the bride. It is around ± 92,5 km (wâlîghâ’ib). The wâlî transposition legality of a marriage, from wâlînasab to wâlîmuhakkam by denying the wâlîhâkim, needs to study from the perspective of Syâfi’î school of law itself. Abstrak Pada masyarakat Madura, terdapat beberapa peristiwa pernikahan sirrî dengan menggunakan wâlîmuhakkam yang didasarkan pada ketentuan hukum (fikih) terutama mazhab Syâfi’î. Pernikahan dengan cara tersebut diyakini sebagai cara yang sah meski keberadaan wâlîmuhakkam tidak dikenal dalam peraturan perundang-undangan yang berlaku di Indonesia. Alasan yang jamak digunakan adalah wali tidak mau menikahkan (wali ‘adlal) dan/atau keberadaan wali sudah memenuhi jarak 2 marhalah (masâfat al-qashr) dengan calon mempelai wanita yaitu ± 92,5 km (wâlîghâ’ib). Perpindahan perwalian dalam pernikahan dari wali nasab kepada wâlîmuhakkam tersebut –dengan ‘menafikan’ posisi wali hakim– perlu ditelaah keabsahannya dari sudut pandang mazhab Syâfi’î sendiri.   Kata Kunci: Wâlînasab, wâlîhâkim dan wâlîmuhakkam, mazhab Syâfi’î